2007
DOI: 10.1021/ja077389b
|View full text |Cite
|
Sign up to set email alerts
|

Catalytic C−C Coupling via Transfer Hydrogenation:  Reverse Prenylation, Crotylation, and Allylation from the Alcohol or Aldehyde Oxidation Level

Abstract: We report byproduct-free carbonyl reverse prenylation, crotylation, and allylation from the alcohol oxidation state via alcohol−allene hydrogen autotransfer. Specifically, exposure of alcohols 1a−6a to 1,1-dimethylallene, methylallene, and allene in the presence of [Ir(cod)(BIPHEP)]BARF (5−7.5 mol %) delivers reverse prenylation products 1c−6c, crotylation products 1d−3d, and allylation product 1e. Similarly, under the conditions of transfer hydrogenation employing isopropanol as terminal reductant, aldehydes … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
53
0
6

Year Published

2008
2008
2018
2018

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 158 publications
(61 citation statements)
references
References 38 publications
2
53
0
6
Order By: Relevance
“…30 In 2008, the first ruthenium catalyzed reactions of this type were developed (Scheme 2). Specifically, it was found that exposure of alcohols to 1,3-dienes in the presence of catalysts derived from HClRu(CO) (PPh 3 ) 3 and various phosphine ligands resulting in hydrogen transfer to furnish aldehydeallylruthenium pairs that combine to form homoallylic alcohols as single regioisomers.…”
Section: Conversion Of Primary Alcohols To Secondary Alcoholsmentioning
confidence: 99%
“…30 In 2008, the first ruthenium catalyzed reactions of this type were developed (Scheme 2). Specifically, it was found that exposure of alcohols to 1,3-dienes in the presence of catalysts derived from HClRu(CO) (PPh 3 ) 3 and various phosphine ligands resulting in hydrogen transfer to furnish aldehydeallylruthenium pairs that combine to form homoallylic alcohols as single regioisomers.…”
Section: Conversion Of Primary Alcohols To Secondary Alcoholsmentioning
confidence: 99%
“…Remarkably, under transfer hydrogenation conditions employing 2-propanol as the terminal reductant, iridium-catalyzed reductive coupling of 1,1-dimethylallene to aldehydes occurs efficiently to deliver the products of reverse prenylation [86]. Even more surprising, under identical conditions but in the absence of 2-propanol, 1,1-dimethylallene engages in direct coupling to alcohols to furnish the very same set of reverse prenylated adducts [86].…”
Section: Hydrogenative Allylation Of Carbonyl Compoundsmentioning
confidence: 99%
“…Even more surprising, under identical conditions but in the absence of 2-propanol, 1,1-dimethylallene engages in direct coupling to alcohols to furnish the very same set of reverse prenylated adducts [86]. Whereas attempted allene-aldehyde reductive coupling to furnish products of allylation and crotylation suffers from over-reduction of the olefinic adduct under conditions that employ gaseous hydrogen as the terminal reductant, under the conditions of transfer hydrogenation and hydrogen autotransfer over-reduction is not observed (Scheme 8.17).…”
Section: Hydrogenative Allylation Of Carbonyl Compoundsmentioning
confidence: 99%
See 1 more Smart Citation
“…[13,14] Hydrierende Carbonylallylierung mit Allenen als Allyldonoren (Schema 6,oben). [16] Es wurde gemutmaßt, dass eine direkte C-Allylierung von Alkoholen durch transferhydrierende C-C-Kupplungen erreicht werden könnte, indem ein alkoholischer Reaktant gleichermaßen als Wasserstoffdonor und Aldehydvorstufe fungiert. Tatsächlich wurde gefunden, dass Alkohole in Gegenwart eines kationischen Iridiumpräkatalysators und eines basischen Additivs direkt an 1,1-Dimethylallen kuppeln.…”
unclassified